Concentrator Photovoltaic System: Optical Characterisation - Ng, Juin Lerg (2020)
In this study, the optical characteristics of an ultra-high concentrator photovoltaic (UHCPV) system such as the uniformity of flux distribution, spillage loss, solar concentration ratio (SCR), tolerance angle against suntracking error, tolerance length against focal distance deviation and tolerance angle against slope error of NIDC quadrant have been explored using the raytracing software TracePro. In the simulation, the UHCPV system has a primary optical element (POE) consisting of 480 facet mirrors forming the non-imaging dish concentrator (NIDC) and a secondary optical element (SOE) consisting of a 2 × 2 array of B270 Schott glass crossed compound parabolic concentrator (CCPC). The NIDC can focus the sunlight into a uniformly illuminated area of 30